Red Chittagong Cattle: An Indigenous Breed to Help Tackle the Challenges of Modern Animal Production Systems - Das, Nani Gopal; Islam, Mohammed R.; Sarker, Nathu Ram; Jalil, Md. Abdul; Clark, Cameron E. F. (Frontiers in Sustainable Food Systems, 2021)
Modern livestock selection is rapidly condensing the indigenous cattle gene pool. This trend limits the options for future genetic selection to benefit both animal well-being and farmer challenges. Here we reveal the potential of Red Chittagong cattle (RCC), a native genotype of Bangladesh, for tackling these current and pending challenges. Red Chittagong cattle are reddish in color and small in size with mature bulls and cows weighing 342 and 180 kg from birth weights of 16 and 14 kg, respectively. Whilst low mean levels of milk production of 618 L across a 228-day lactation are recorded so are high levels of milk protein (3.8%) and fat (4.8%) with offered feed types typically low in nutritive value, particularly crude protein. However, one in five cows under farm condition yield >1,000 L/lactation. Alongside high levels of milk protein and fat, other key features of this breed include resistance to common diseases and parasites with a high level of adaptation to agro-ecological conditions. As opposed to other indigenous breeds, there is currently high genetic variation in the RCC population, and associated variation in productive and reproductive traits highlighting the opportunity for development through long-term breeding programs alongside improved management conditions. Such efforts would enable this breed to become a global resource for tackling the challenges of modern animal production systems. In addition, further work is required to reveal the demographic distribution of the breed, potential production levels through the provision of improved diets and the mechanisms enabling disease resistance and digestibility of feeds.